2006
DOI: 10.1103/physrevb.73.014104
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties ofCaMoO4: Lattice dynamics and synchrotron powder diffraction studies

Abstract: The structure of calcium molybdate was studied by means of synchrotron based high-resolution powder diffraction methods in the temperature range 12-300 K. The scheelite structure type was confirmed for CaMoO 4 in the temperature region investigated and no structural anomalies were observed. Thermal expansion coefficients extracted from the thermal dependencies of the cell sizes are found to be in good agreement with the predictions from our lattice dynamics calculations that form the background for microscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 51 publications
2
51
0
1
Order By: Relevance
“…Each layer has a two-dimensional CsCl arrangement of a Ca cation and an anion complex (MoO 4 ) surrounded by eight ions of opposite sign (see fig. 1 in [16]). There are at least two optimal directions for seeding and further growth of the CaMoO 4 crystal.…”
Section: Crystal Growthmentioning
confidence: 94%
“…Each layer has a two-dimensional CsCl arrangement of a Ca cation and an anion complex (MoO 4 ) surrounded by eight ions of opposite sign (see fig. 1 in [16]). There are at least two optimal directions for seeding and further growth of the CaMoO 4 crystal.…”
Section: Crystal Growthmentioning
confidence: 94%
“…[7][8][9][10] More recently, CM is being studied as a material for cryogenic phonon scintillation detector applications. 11 By using time-resolved spectroscopy, Leonelli and Brebner proposed a model to describe the luminescence process whereby electrons form small polarons that interact with holes to produce self-trapped excitons (STEs), with the recombination of STEs resulting in the visible emission, either immediately or after being trapped for a certain time by impurities and defects. 12,13 As a result of previous studies of photoluminescence (PL) properties, we recently reported that two mechanisms were found to be responsible for PL emission in CaWO 4 and CM powders.…”
Section: Introductionmentioning
confidence: 99%
“…Чтобы проверить достоверность применения (2), мы провели аналогичную процедуру с данными работы [19] для CaMoO 4 , взятыми в диапазоне T ∼ 300−1273 K. Полученные нами a(T ) и c(T ) неплохо совпадают с экспериментальными результатами [20] в области T = 10−300 K. Используя (2) с определенными выше a i и c i , мы расcчитали параметры решетки SrMoO 4 при нужных T , а затем и сферические координаты R, θ, ϕ ближайших к Gd 3+ 8 ионов кислорода (O 2− ) в чистой решетке SrMoO 4 . Координаты x, y, z этих O 2− взяты из данных работы [21].…”
Section: модельные расчетыunclassified